Corrosion engineering - Cicek, Volkan (Scrivener-Wiley, 2014)
"Corrosion Engineering is a must-have reference book for the engineer in the field that covers the corrosion process with its contemporary aspects with respect to both of its scientific and engineering aspects. It is also a valuable textbook that could be used in an engineering or scientific course on corrosion at the university level"--